Transformasi Narasi Pasca Blackout: Framing Media Lokal Bali terhadap Agenda Bali Mandiri Energi 2025 - Sarahswati, Made Dwi Kanaka; Anggreswari, Ni Putu Yunita; Maheswari, Anak Agung Istri Agung; Wedananta, Kadek Adyatna (LPPM Institut Pendidikan Nusantara Global, 2025)
This research analyzes how local Balinese media frame the narrative surrounding Bali Mandiri Energi following the 2025 blackout that paralyzed the island for more than ten hours. The study applies Robert Entman’s framing theory to examine how two major local news outlets, Radar Bali and Bali Post, constructed meaning and directed public attention toward the government’s energy independence agenda. Using a theoretic descriptive approach, the study identifies key framing devices such as problem definition, causal interpretation, moral evaluation, and treatment recommendation. Findings reveal that both media positioned the blackout not merely as a technical failure, but as a symbolic crisis that exposed Bali’s energy dependency on Java. The discourse of Bali Mandiri Energi was amplified through positive moral framing, portraying the initiative as a collective breakthrough rooted in regional pride and resilience. However, subtle differences appear: Radar Bali emphasized political accountability, while Bali Post foregrounded cultural and environmental narratives. The research concludes that local media framing played a strategic role in transforming a regional crisis into a narrative of innovation and self-reliance.